(untitled) (Revista de Ciências Agroveterinárias, 2015)
The no-till reduces erosion compared to conventional tillage; however, nutrient losses in runoff are source of environmental contamination. This study aimed to evaluate the effect of using furrow shank in the seeder on the runoff and water infiltration into soil, in no-till, and quantify the levels and losses of soluble phosphorus in runoff at different rates of pig slurry applied to the soil surface. The experiment was conducted in 2009, in São José do Cerrito/SC, Brazil, in Nitosol soil. Simulated rainfall with intensity of 70 mm h-1 was applied for 1.5 h in plots with the seeder equipped with double disks (SDD) and with double disc and furrow shank (SDH). In addition, before the rain, rates of 0; 30; and 60 m3 ha-1 of pig slurry were applied in SDH and rates of 15; 45; and 75 m3 ha-1 were applied in SDD. During the runoff, flow rate was measured and samples were collected for determination of soluble phosphorus. The maximum rate and volume of runoff were smaller, while the runoff start time, the total infiltration and the basic rate of water infiltration into the soil were higher in SDH than SDD. The levels and the loss of soluble phosphorus in runoff increased proportionally with the rate of pig slurry; however, the use of furrow shank in the seeder reduced the levels and the loss of the element in runoff.